A chromium-titanium carbide metal ceramic and its preparation method

Prepare CR3C2-TIC composite solid soluble powder through high-energy ball mills, and mixed with Ni powder for sintering, solve the problem of growing up the hard phase grain of CR3C2-NI metal ceramics, and realized the high-powered performance and high-powered performance of chromium carbonized titanium ceramics and Low pore rate is suitable for various industrial applications.

CN116397124BActive Publication Date: 2025-01-28SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310473503.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2025-01-28
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

The crystal grains of Cr3C2 hard phase in the sintered microstructure of existing Cr3C2-Ni cermets grow abnormally, resulting in deterioration of mechanical properties. In addition, the traditional single carbide component addition method is difficult to achieve uniform mixing of elements, and the hard phase cannot be effectively regulated. dissolution and precipitation process.

Method used

By grinding CR2O3, TiO2 and charcoal black, the CR3C2-TIC composite solid solid soluble powder is obtained, and mixed with Ni powder and molding agents are performed for granules, molding and sintering to prepare chrome carbide titanium-titanium ceramics. This method By promoting the solid solution of TI atoms and CR atoms in the process of carbon heat reduction, it inhibits the abnormal growth of CR3C2 grains, reduces the sintering pore rate, and strengthens the bonding phase.

Benefits of technology

The high strength, hardness, and toughness of chromium carbide titanium ceramics can be achieved. The bending strength can reach 1113MPa, the Highness can reach 1084MPA, and the fracture toughness can reach 8.06MPa · M1/2. It is suitable for cutting, mining, marine development, mechanical machinery Sealing and aerospace areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116397124B_ABST
    Figure CN116397124B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of hard material preparation, and specifically relates to a chromium carbide titanium metal ceramic and a preparation method thereof. The present invention uses chromium trioxide, titanium dioxide and carbon black as raw materials for high-energy ball milling to obtain a high-activity mixed powder, and manufactures more active atomic sites on the surface of the mixed powder to promote the solid solution of titanium atoms into the chromium carbide lattice, and the solid solution of chromium atoms into the titanium carbide lattice. The obtained chromium carbide-titanium carbide composite solid solution powder plays a positive role in reducing the dissolution and precipitation rate of Cr3C2 in the bonding phase, can inhibit the abnormal growth of Cr3C2 grains during the sintering process, eliminate residual pores, reduce the sintering porosity, strengthen the bonding phase, so that the strength, hardness and toughness of the chromium carbide titanium metal ceramic are comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hard material preparation, and specifically relates to a chromium titanium carbide metal ceramic and a preparation method thereof. Background Art

[0002] WC-Co is the most widely studied cermet (also known as cemented carbide). It is widely used in cutting and mining tools due to its excellent mechanical properties such as high hardness and high strength, so it is also called "industrial teeth". However, WC-based cemented carbide has poor acid and alkali corrosion resistance and high temperature oxidation resistance, which limits its further industrial application. In addition, W and Co resources have been gradually exhausted due to long-term development and application, and there is an urgent need to develop new W-free cermets that can be used under extreme service conditions.

[0003] Cr3C2-based cermets have good acid and alkali corrosion resistance and high temperature oxidation resistance, and have broad application prospects in the fields of marine development, mechanical sealing, and aerospace. However, the sintered microstructure of traditional Cr3C2-Ni cermets shows abnormal growth of Cr3C2 hard phase grains and high porosity, which leads to deterioration of its mechanical properties. Taking Cr3C2-20Ni cermets as an example, the bending strength of vacuum sintering is only 500-700MPa, which is difficult to achieve large-scale application.

[0004] In order to solve the above technical difficulties, the prior art usually adds second phase carbide (such as MoC and VC, etc.) powder to inhibit the long chain abnormal growth of Cr3C2 grains. However, this single carbide component addition method makes it difficult to achieve uniform mixing of the added elements and the Cr3C2 hard phase at the molecular level during the ball milling mixing process, and cannot effectively regulate the dissolution and precipitation process of the hard phase in the Ni bonding phase, thereby having a very limited effect on improving the mechanical properties of chromium carbide-based metal ceramics. Summary of the invention

[0005] The object of the present invention is to provide a chromium-titanium carbide metal ceramic and a preparation method thereof. The chromium-titanium carbide metal ceramic provided by the present invention has high strength, high hardness, good toughness and excellent comprehensive mechanical properties.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing chromium-titanium carbide metal ceramics, comprising the following steps:

[0008] (1) Cr2O3, TiO2 and carbon black are subjected to high-energy ball milling and then subjected to carbothermal reduction reaction and crushing in sequence to obtain Cr3C2-TiC composite solid solution powder;

[0009] The rotation speed of the high energy ball mill is not less than 1000r / min;

[0010] (2) The Cr3C2-TiC composite solid solution powder, the binder phase and the forming agent are mixed and then granulated, formed and sintered in sequence to obtain chromium carbide titanium metal ceramics.

[0011] Preferably, the temperature of the carbon thermal reduction reaction is 1200-1500° C., and the insulation time is 1-3 hours.

[0012] Preferably, in step (1), the mass ratio of Cr2O3 to TiO2 is 50-60:10-20;

[0013] The mass ratio of Cr2O3 to carbon black is 50-60:20-30.

[0014] Preferably, in step (2), the mass ratio of the Cr3C2-TiC composite solid solution powder to the binder phase is 70-85:15-30;

[0015] The ratio of the total mass of the Cr3C2-TiC composite solid solution powder and the binder phase to the mass of the forming agent is 100:1.5-2.5.

[0016] Preferably, the particle size of the Cr3C2-TiC composite solid solution powder is 0.5 to 3 μm;

[0017] The bonding phase is Ni powder; the particle size of the Ni powder is 0.2 to 1.5 μm;

[0018] The molding agent includes one of polyethylene glycol, paraffin and rubber.

[0019] Preferably, the sintering in step (2) includes a first heating, a first heat preservation sintering, a second heating, a second heat preservation sintering, a third heating and a third heat preservation sintering; the temperature of the first heat preservation sintering is 450-650°C, and the heat preservation time is 0.5-1h; the temperature of the second heat preservation sintering is 1000-1100°C, and the heat preservation time is 0.5-1.0h; the temperature of the third heat preservation sintering is 1200-1300°C, the pressure is 2-4MPa, the sintering atmosphere is an inert gas, and the heat preservation time is 0.5-1.5h.

[0020] Preferably, the molding method is compression molding; the compression molding pressure is 7 to 10 MPa, and the holding time is 10 to 30 s.

[0021] Preferably, the target particle size of the granulation is 2 to 4 μm.

[0022] The present invention also provides a chromium-titanium carbide metal ceramic obtained by the preparation method described in the above scheme, wherein the Cr3C2 grains of the chromium-titanium carbide metal ceramic are not larger than 6 μm.

[0023] The present invention also provides the application of the chromium-titanium carbide metal ceramics described in the above scheme in cutting, mining, marine development, mechanical sealing and aerospace.

[0024] The present invention provides a method for preparing chromium-titanium carbide metal ceramics. The present invention uses Cr2O3, TiO2 and carbon black as raw materials for high-energy ball milling to obtain a highly active "oxide-carbon" mixed powder, obtains more active atomic sites on the surface of the mixed powder, promotes the solid dissolution of Ti atoms into the Cr3C2 lattice during the carbon thermal reduction process, and the solid dissolution of Cr atoms into the TiC lattice during the carbon thermal reduction process, and the obtained Cr3C2-TiC composite solid solution powder is used as a hard phase, mixed with a binder phase and a molding agent for granulation, molding and sintering. The Cr3C2-TiC composite solid solution powder plays a positive role in reducing the dissolution and precipitation rate of Cr3C2 in the binder phase, can inhibit the abnormal growth of Cr3C2 grains during the sintering process, eliminate residual pores, reduce the sintering porosity, strengthen the binder phase, so that the strength, hardness and toughness of the chromium-titanium carbide metal ceramics are comprehensively improved. The results of the examples show that the chromium-titanium carbide metal ceramics prepared by the preparation method provided by the present invention have excellent comprehensive mechanical properties, and their bending strength can reach 1113MPa, Vickers hardness can reach 1084MPa, and fracture toughness can reach 8.06MPa·m 1 / 2 The preparation method provided by the present invention can realize large-scale production by using traditional cemented carbide production equipment, has low production cost, and is convenient for industrial promotion and application.

[0025] The present invention also provides a chromium carbide titanium metal ceramic obtained by the preparation method described in the above scheme. The chromium carbide titanium metal ceramic of the present invention uses Cr3C2-TiC composite solid solution powder as a hard phase, adds a bonding phase and a molding agent, and is bonded and molded into a green body. The Cr3C2-TiC composite solid solution powder plays a positive role in reducing the dissolution and precipitation rate of Cr3C2 in the bonding phase, can inhibit the abnormal growth of Cr3C2 grains during the sintering process, eliminate residual pores, reduce sintering porosity, and strengthen the bonding phase, thereby comprehensively improving the strength, hardness and toughness of the chromium carbide titanium metal ceramic.

[0026] The present invention also provides the application of the chromium-titanium carbide metal ceramics in the above scheme in cutting, mining, marine development, mechanical sealing and aerospace. The chromium-titanium carbide metal ceramics provided by the present invention have high strength, high hardness, good toughness and excellent comprehensive performance, and are suitable for cutting, mining, marine development, mechanical sealing and aerospace and other fields, with obvious economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0028] Figure 1 This is a microstructure morphology diagram of the 80(Cr3C2-TiC)-20Ni metal ceramic prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The present invention provides a method for preparing chromium-titanium carbide metal ceramics, comprising the following steps:

[0030] (1) Cr2O3, TiO2 and carbon black are subjected to high-energy ball milling and then subjected to carbothermal reduction reaction and crushing in sequence to obtain Cr3C2-TiC composite solid solution powder;

[0031] The rotation speed of the high energy ball mill is not less than 1000r / min;

[0032] (2) The Cr3C2-TiC composite solid solution powder, the binder phase and the forming agent are mixed and then granulated, formed and sintered in sequence to obtain chromium carbide titanium metal ceramics.

[0033] The present invention performs carbothermal reduction reaction and crushing in sequence after high-energy ball milling of Cr2O3, TiO2 and carbon black to obtain Cr3C2-TiC composite solid solution powder. The present invention has no special provisions on the sources of the Cr2O3, TiO2 and carbon black, and conventional commercially available powdered solids in the art can be used.

[0034] In the present invention, the mass ratio of Cr2O3 and TiO2 is preferably 50-60:10-20, more preferably 52-58:12-18, and further preferably 55-56:15-16; the mass ratio of Cr2O3 and carbon black is preferably 50-60:20-30, more preferably 52-58:22-28, and further preferably 55-56:25-26.

[0035] In the present invention, the rotation speed of the high energy ball mill is not less than 1000r / min, preferably 1000-1200r / min, more preferably 1100-1200r / min, and the time is preferably 1.5-2.5h, more preferably 1.8-2.2h, and further preferably 2h; the device for the high energy ball mill is preferably a high energy ball mill controlled by frequency conversion. The present invention has no special requirements for the quality of the single ball milling powder of the high energy ball mill, and it can be selected according to less than two-thirds of the volume of the high energy ball mill tank. The present invention limits the rotation speed and time of the high energy ball mill to the above range, which is conducive to fully high energy activation of the mixed powder of raw materials Cr2O3, TiO2 and carbon black to obtain a highly active mixture powder.

[0036] The present invention limits the amount of Cr2O3, TiO2 and carbon black to the above range, and obtains a high-activity mixed powder through high-energy ball milling, which can obtain more active atomic sites on the surface of the mixed powder, and improve the surface activation energy of the powder while mixing the solid materials evenly, promoting the solid dissolution of Ti atoms into the Cr3C2 lattice and the solid dissolution of Cr atoms into the TiC lattice, thereby obtaining a Cr3C2-TiC composite solid solution powder.

[0037] In the present invention, the temperature of the carbon thermal reduction reaction is preferably 1200-1500°C, more preferably 1300-1400°C, and further preferably 1350°C, and the holding time is preferably 1-3h, more preferably 1.5-2.5h, and further preferably 2h; the device for the carbon thermal reduction reaction is preferably a vacuum carbon tube furnace; and the carbon thermal reduction reaction is preferably carried out under vacuum conditions. The present invention has no special requirements for the vacuum degree of the vacuum, and it can be selected according to the routine. The present invention adopts vacuum conditions for the carbon thermal reduction reaction, which can avoid the adverse effects of oxygen in the air on the carbon thermal reduction reaction, and ensure that Cr2O3 is reduced and carbonized to obtain Cr3C2.

[0038] In the present invention, the particle size of the Cr3C2-TiC composite solid solution powder is preferably 0.5-3 μm, more preferably 1.0-2.5 μm, and further preferably 1.5-2.0 μm. The present invention limits the particle size of the Cr3C2-TiC composite solid solution powder to the above range, which is conducive to obtaining a dense metal ceramic material.

[0039] In the present invention, the target particle size of the crushing is preferably consistent with the particle size of the Cr3C2-TiC composite solid solution powder; the present invention has no special provisions on the crushing method, and the solid material crushing method familiar to those skilled in the art is used to crush the material to the target particle size; in an embodiment of the present invention, the crushing method is preferably ball milling; the present invention has no special provisions on the ball milling method, and the large block material is crushed to the target particle size by the ball milling method familiar to those skilled in the art. In a specific embodiment of the present invention, the ball milling method is preferably planetary ball milling; the ball milling medium of the ball milling is preferably ethanol and cemented carbide grinding balls; the frequency of the ball milling is preferably 23.5Hz, and the ball milling time is preferably 13h. The present invention obtains Cr3C2-TiC composite solid solution powder by crushing, and uses it as a raw material to prepare chromium carbide titanium metal ceramics, which can significantly optimize the mechanical properties of chromium carbide titanium metal ceramics.

[0040] In the present invention, the product is preferably dried after the crushing; the present invention has no special provisions on the drying method, and a drying method well known to those skilled in the art can be used to remove the ball milling aid used in the ball milling process. In a specific embodiment of the present invention, the drying temperature is preferably 70° C., and the holding time is preferably 2 hours.

[0041] After obtaining the Cr3C2-TiC composite solid solution powder, the present invention sequentially granulates, molds and sinters the Cr3C2-TiC composite solid solution powder, the binder phase and the molding agent after mixing to obtain a chromium carbide titanium metal ceramic. In the present invention, the binder phase is preferably Ni powder; the particle size of the Ni powder is preferably 0.2 to 1.5 μm, more preferably 0.5 to 1.2 μm, and further preferably 0.8 to 1.0 μm. The present invention limits the particle size of the binder phase to the above range, which is conducive to obtaining a densely structured metal ceramic material.

[0042] In the present invention, the molding agent preferably includes one of polyethylene glycol, paraffin wax and rubber, and more preferably polyethylene glycol. The present invention facilitates the mixing and molding of the Cr3C2-TiC composite solid solution powder and the binder phase to obtain a green body by adding the molding agent to the raw materials.

[0043] In the present invention, the mass ratio of the Cr3C2-TiC composite solid solution powder to the binder phase is preferably 70-85:15-30, more preferably 73-82:18-27, and further preferably 76-79:21-24. The present invention limits the amount of the binder phase to the above range, which is beneficial to improving the comprehensive properties of the chromium carbide titanium metal ceramic.

[0044] In the present invention, the total mass ratio of the Cr3C2-TiC composite solid solution powder and the binder phase to the mass ratio of the molding agent is preferably 100:1.5-2.5, more preferably 100:1.7-2.2, and further preferably 100:1.9-2.1. The present invention limits the amount of the molding agent to the above range, which is conducive to fully bonding and molding the Cr3C2-TiC composite solid solution powder and the Ni powder.

[0045] In the present invention, the mixing method of the Cr3C2-TiC composite solid solution powder, the binder phase and the molding agent is preferably ball milling. In the present invention, the ball milling medium of the ball milling preferably includes ethanol and carbide grinding balls; the amount of ethanol added (accounting for the total mass of the mixture obtained by mixing the Cr3C2-TiC composite solid solution powder, the binder phase and the molding agent) is preferably 20-40%, more preferably 25-30%; the rotation speed of the ball milling is preferably 70-90r / min, more preferably 80r / min, the ball-to-material ratio is preferably 6-8:1, more preferably 7:1, the time is preferably 20-30h, more preferably 24h; after the ball milling, the obtained ball milling product is preferably dried; the drying temperature is preferably 50-80°C, more preferably 70°C, and the insulation time is preferably 1-3h, more preferably 2h.

[0046] In the present invention, the target particle size of the granulation is preferably 2-4 μm, more preferably 2.5-3.5 μm, and further preferably 3 μm. The present invention has no special provisions on the granulation method, and the raw material can be made into granules by using a granulation method well known to those skilled in the art.

[0047] In the present invention, the molding method is preferably press molding; the pressure of the press molding is preferably 7-10 MPa, more preferably 8-9 MPa, and the holding time is preferably 10-30 s, more preferably 15-25 s. The present invention has no special provisions for the press molding method, and a press molding method well known to those skilled in the art can be used to obtain a metal ceramic body. The present invention limits the pressure of the press molding to the above range, which is conducive to obtaining a metal ceramic body.

[0048] In the present invention, the sintering preferably includes a first heating, a first heat preservation sintering, a second heating, a second heat preservation sintering, a third heating and a third heat preservation sintering; the temperature of the first heat preservation sintering is preferably 450-650°C, more preferably 550-600°C, and the heat preservation time is preferably 0.5-1h, more preferably 0.5-0.8h. The present invention can remove the forming agent in the material by performing the first heat preservation sintering.

[0049] In the present invention, the temperature of the second heat preservation sintering is preferably 1000-1100°C, more preferably 1030-1070°C, and the heat preservation time is preferably 0.5-1.0h, more preferably 0.5-0.8h. By performing the second heat preservation sintering, the present invention can fully carry out the deoxidation reaction in the system and eliminate the adverse effects of oxygen on the performance of the metal ceramic.

[0050] In the present invention, the temperature of the third heat preservation sintering is preferably 1200-1300°C, more preferably 1250-1280°C, the pressure is preferably 3-4MPa, more preferably 3.5MPa, the sintering atmosphere is preferably an inert gas, and the heat preservation time is preferably 0.5-1.5h, more preferably 1.0-1.2h; the inert gas is preferably argon; the amount of the inert gas charged is preferably 3-5MPa, more preferably 3-4MPa. The present invention can eliminate the residual pores that are not completely eliminated during the liquid phase sintering process by performing the third heat preservation sintering and charging the inert gas for pressure sintering. The present invention can eliminate the residual pores that are not completely eliminated during the liquid phase sintering process by charging the inert gas during the sintering process.

[0051] In the present invention, the heating rate of the first heating is preferably 2.0-5.0°C / min, more preferably 3.0-4.0°C / min; the heating rate of the second heating is preferably 2.0-5.0°C / min, more preferably 3.0-4.0°C / min; the heating rate of the third heating is preferably 2.0-5.0°C / min, more preferably 3.0-4.0°C / min. The present invention limits the heating rate to the above range, which can avoid the adverse effect of too fast heating rate on the performance of the sintered body.

[0052] The present invention also provides a chromium carbide titanium metal ceramic obtained by the preparation method described in the above scheme, wherein the Cr3C2 grains of the chromium carbide titanium metal ceramic are not larger than 6μm. In the present invention, the porosity of the Cr3C2 grains of the chromium carbide titanium metal ceramic is preferably 1-2%. The Cr3C2 grains of the chromium carbide-based metal ceramic provided by the present invention are small, and the porosity is low. The flexural strength can reach 1113MPa, the Vickers hardness can reach 1084MPa, and the fracture toughness can reach 8.06MPa·m 1 / 2 .

[0053] The present invention also provides the application of the chromium-titanium carbide metal ceramics described in the above scheme in cutting, mining, marine development, mechanical sealing and aerospace.

[0054] The chromium-titanium carbide metal ceramic provided by the present invention has high strength, high hardness, good toughness and excellent comprehensive performance, and can be used in cutting tools, mining equipment, mechanical equipment, spacecraft and the like.

[0055] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0056] Example 1

[0057] A method for preparing chromium-titanium carbide metal ceramics comprises the following steps:

[0058] (1) Weighing 101.32 g of Cr2O3 powder, 26.68 g of TiO2 powder and 46.72 g of carbon black powder (the mass ratio of Cr2O3, TiO2 and carbon black is 58:15:27), loading them into a high-energy ball mill for high-energy ball milling to obtain a high-activity high mixed powder, subjecting the mixed powder to a carbothermal reduction reaction, vacuum carbothermal reduction at 1200°C for 2 h, obtaining a carbothermal reduction product, a Cr3C2-TiC composite block, loading it into a stainless steel ball mill, adding alcohol and cemented carbide grinding balls for planetary ball milling, the ball milling frequency is 23.5 Hz, the ball milling time is 13 h, after the ball milling is completed, the ball milled mixture is dried at 70°C for 2 h, obtaining a Cr3C2-TiC composite solid solution powder (particle size is 1.0 to 3.0 μm);

[0059] (2) 80 g of the Cr3C2-TiC composite solid solution powder prepared in step (1) and 20 g of the binder phase Ni powder (particle size of 0.5-1.0 μm) (the Ni powder accounts for 20% of the total mass of the Ni powder and the Cr3C2-TiC composite solid solution powder) are weighed and placed in a ball mill. Alcohol and carbide grinding balls are added to a common ball mill for ball milling for 20 h at a ball milling speed of 80 r / min. After the ball milling, the ball milled mixture is dried at 70° C. for 3 h, 1.8 g of polyethylene glycol (PEG4000) molding agent is added and granulated (the molding agent PEG4000 accounts for 1.8% of the total mass of the Cr3C2-TiC composite solid solution powder and the Ni powder), and then a hydraulic press is used to press the mixture at a pressure of 8 MPa. The pellets are pressed into a metal ceramic body; the metal ceramic body is placed in a low-pressure sintering furnace for sintering, and the sintering process is as follows: first, the temperature is increased to 600°C at a heating rate of 3.5°C / min, and the temperature is kept for sintering for 0.5h, then the temperature is increased to 1050°C at a heating rate of 3.5°C / min, and sintered at this temperature for 0.5h, and finally the temperature is increased to 1150°C at a heating rate of 3.5°C / min. When the temperature reaches this temperature, 3MPa of argon is filled, and finally, pressure sintering is carried out at a temperature of 1230°C and a pressure of 3MPa for 1h to obtain chromium carbide titanium metal ceramics, whose component ratio is (64Cr3C2-16TiC)-20Ni, and it is named 80(Cr3C2-TiC)-20Ni metal ceramics.

[0060] Figure 1The microstructure morphology of the 80(Cr3C2-TiC)-20Ni-based cermet prepared in this embodiment is shown in FIG. Figure 1 It can be seen that the hard phase structure and bonding phase in the metal ceramic organization are evenly distributed, and defects such as cracks and pores in the organization are basically eliminated.

[0061] Comparative Example 1

[0062] The difference between this comparative example and Example 1 is that two commercially available single-component powders (Cr3C2+TiC) are directly used to carry out step (2), and the other conditions are consistent with Example 1 to obtain (64Cr3C2-16TiC)-20Ni metal ceramics.

[0063] Comparative Example 2

[0064] In order to more intuitively compare the improvement of the performance of Cr3C2-Ni cemented carbide by adding (Cr, Ti, W)3C2 composite solid solution powder, no inhibitor powder was added in this comparative example, and the other conditions were kept consistent with Example 1 to obtain 80Cr3C2-20Ni metal ceramic.

[0065] The mechanical properties of the metal ceramics obtained in Example 1 and Comparative Examples 1-2 were tested. The test results are shown in Table 1.

[0066] (1) Test method for flexural strength:

[0067] Before the test, the sample was polished to a standard spline and placed on a horizontal special test fixture with a span of 15 mm. A short-term static force was then applied at the midpoint of the span at a speed of no more than 1600 N per second until the spline broke. The maximum force at the time of spline fracture was recorded and the width and height of the cross section near the spline fracture were measured.

[0068] This experiment uses a WDW-50 electronic universal testing machine to test the bending strength of the specimen. The size of the specimen to be tested is 20mm×6.5mm×5.25mm, and the loading speed of the force is 500N·s -1 , the span is 14.5mm, at least 5 splines are tested in each group and the arithmetic mean is taken, and the value is retained to ten digits; the calculation formula for flexural strength is:

[0069] TRS=3FL / (2bh 2 )

[0070] Where TRS is the flexural strength (MPa),

[0071] F is the load when the spline breaks (N),

[0072] L is the distance (span) between the two supporting points (mm),

[0073] b is the width of the spline (mm),

[0074] h is the height of the spline (mm).

[0075] (2) Vickers hardness test method:

[0076] The principle of the Vickers hardness tester is to press a right pyramid diamond indenter with a relative angle of 136° into the surface of the sample under the action of a set load P, maintain the pressure for 10 seconds and then remove the load, measure the diagonal length D of the indentation, calculate the surface area of ​​the indentation, and finally calculate the average pressure on the indentation surface, which is the Vickers hardness. This experiment uses the HV-30Z model Vickers hardness tester to measure the hardness. Each group of samples tests at least 5 sample strips, and each sample is measured at 5 points. The arithmetic mean is taken and retained to the tenth digit; the calculation formula of Vickers hardness is:

[0077] HV=1.8544×P / D 2

[0078] Where HV is the Vickers hardness (Kgf·mm -2 ),

[0079] P is the applied load (Kgf),

[0080] D is the diagonal length of the indentation (mm).

[0081] (3) Fracture toughness test method:

[0082] The fracture toughness of the alloy was tested by the indentation method. The indentation of the Vickers hardness test and the cracks generated were used for calculation. Five points were taken on the surface of each cemented carbide sample for testing, and the arithmetic mean of the calculated fracture toughness values ​​was taken as the fracture toughness value of the sample. The calculation formula for fracture toughness is as follows:

[0083] K IC =0.15*(HV 30 / L i ) 1 / 2

[0084] In the formula, K IC is the fracture toughness (MPa·m 1 / 2 ),

[0085] HV 30 The Vickers hardness of the alloy (Kgf·mm) with a load of 30Kg -2 ),

[0086] L i is the total length of the alloy crack (mm).

[0087] Table 1 Performance test results of metal ceramics obtained in Example 1 and Comparative Examples 1-2

[0088]

[0089] According to Table 1, the strength, hardness and toughness of the 80 (Cr3C2-TiC) -20Ni metal ceramic prepared by using the Cr3C2-TiC composite solid solution powder in Example 1 of the present invention are significantly improved, which effectively overcomes the technical deficiency of the prior art that the three mechanical properties cannot be improved at the same time; in addition, through comparative studies, it is found that the addition method of the Cr3C2-TiC composite solid solution is significantly better than a single component mixed component (Comparative Example 1) and no inhibitor powder is added (Comparative Example 2).

[0090] It can be seen from the above embodiments that the chromium carbide titanium metal ceramic provided by the present invention has Cr3C2-TiC composite solid solution powder as the hard phase, which plays a positive role in reducing the dissolution rate of Cr3C2 in the bonding phase, eliminating residual pores, reducing sintering porosity, and strengthening the bonding phase, so that the strength, hardness and toughness of the chromium carbide titanium metal ceramic are comprehensively improved.

[0091] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing chromium-titanium carbide metal ceramics, characterized in that: The following steps are involved: (1) Cr2O3, TiO2 and carbon black are subjected to high-energy ball milling and then subjected to carbothermal reduction reaction and crushing in sequence to obtain Cr3C2-TiC composite solid solution powder; The rotation speed of the high energy ball mill is not less than 1000r / min; (2) mixing the Cr3C2-TiC composite solid solution powder, a binder phase and a forming agent, and then granulating, forming and sintering them in sequence to obtain a chromium carbide titanium metal ceramic; In the step (1), the mass ratio of Cr2O3 to TiO2 is 50-60:10-20; The mass ratio of Cr2O3 to carbon black is 50-60:20-30.

2. The preparation method according to claim 1, characterized in that: The temperature of the carbon thermal reduction reaction is 1200-1500° C., and the insulation time is 1-3 hours.

3. The preparation method according to claim 1, characterized in that: In the step (2), the mass ratio of the Cr3C2-TiC composite solid solution powder to the binder phase is 70-85:15-30; The ratio of the total mass of the Cr3C2-TiC composite solid solution powder and the binder phase to the mass of the forming agent is 100:1.5-2.

5.

4. The preparation method according to claim 1 or 3, characterized in that: The particle size of the Cr3C2-TiC composite solid solution powder is 0.5 to 3 μm; The bonding phase is Ni powder; the particle size of the Ni powder is 0.2 to 1.5 μm; The molding agent includes one of polyethylene glycol, paraffin and rubber.

5. The preparation method according to claim 1, characterized in that: The sintering in step (2) includes a first heating, a first heat preservation sintering, a second heating, a second heat preservation sintering, a third heating and a third heat preservation sintering; The temperature of the first heat preservation sintering is 450-650°C, and the heat preservation time is 0.5-1h; The temperature of the second heat preservation sintering is 1000-1100°C, and the heat preservation time is 0.5-1.0h; The temperature of the third heat-insulating sintering is 1200-1300° C., the pressure is 2-4 MPa, the sintering atmosphere is an inert gas, and the heat-insulating time is 0.5-1.5 h.

6. The preparation method according to claim 1, characterized in that: The molding method is compression molding; the compression molding pressure is 7-10 MPa, and the holding time is 10-30 seconds.

7. The preparation method according to claim 1, characterized in that: The target particle size of the granulation is 2 to 4 μm.

8. The chromium-titanium carbide metal ceramic obtained by the preparation method according to any one of claims 1 to 7, wherein the Cr3C2 grains of the chromium-titanium carbide metal ceramic are not larger than 6 μm.

9. Application of the chromium-titanium carbide metal ceramic according to claim 8 in cutting, mining, marine development, mechanical sealing and aerospace.

Citation Information

Patent Citations

  • Preparation method of plate carbide sosoloid toughening and mischcrystal Ti(C,N)-based cermet

    CN109487141A

  • Ternary boride reinforced Ti-based (C,N) metal ceramic material and preparation method thereof

    CN109576547A